Exploring the Relationship between Social Media Engagement, Customer Reviews, and Brand Perceptions: A Comprehensive Study in Retail Industry - Krisprimandoyo, Denpharanto Agung; Sufa, Siska Armawati; Wardani, Dini Tri; Widiyanto, Sigit (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the intricate relationships between social media engagement, customer reviews, and brand perceptions in the retail industry. Through a qualitative analysis of customer-generated content and social media interactions, key themes and patterns emerged, shedding light on the factors influencing brand sentiment and consumer behavior. The findings highlight the impact of positive brand experiences, strategic social media engagement, user-generated content, transparency, and authenticity in shaping brand perceptions and fostering customer loyalty. The study underscores the importance of delivering exceptional customer experiences, engaging meaningfully on social media platforms, and prioritizing transparency and authenticity to enhance brand perception and build trust in the digital era.